Health and Safety Management at Work of a Catering Services Company - Merino-Moncayo, Mario Enrique (2022)
Currently, in Ecuadorian legislation, safety and health at work has marked notable changes to improve the working conditions of workers through laws and regulations to protect them against occupational risks, the objective is to do so before they are reached to materialize and therefore may cause damage to the health of workers. According to the theoretical analysis carried out, the basic elements of an occupational health and safety management system and its respective implementation methodology are proposed in the Macedonia Catering Services company of Santo Domingo city. This work originates from the absence of internal regulations, technical guides and instruments that regulate adequate management to safeguard the integrity, health and life of personnel. With this legal framework, the company under study is obliged to transform the way it has been managing the health and safety of workers. In this way it will be possible to increase the level of performance by improving the working conditions of the staff.